Effects of small ponds on stream water quality and macroinvertebrate communities - John R. Maxted; Colin H. McCready; Mike R. Scarsbrook (New Zealand Journal of Marine and Freshwater Research, 2005)
Six small constructed ponds (surface area 500–7500 m 2 , catchment area 28–158 ha) in rural and native forest catchments in the Auckland region had poorer water quality than the streams they replaced. Temperature (24°C) and dissolved oxygen (DO) (4 mg/litre) criteria were exceeded for up to 46% and 84% of days, respectively, during a critical 40‐day summer period. The poor conditions found in ponds, even within undeveloped native forest catchments, indicated that the physical characteristics of ponds (e.g., lack of shade, organic sediments) affected water quality independently of other factors (e.g., land use, riparian protection). The frequency and severity of the exceedences were related to pond size, retention time, and catchment land use; the most degraded conditions were found in rural ponds with largest surface areas and longest retention times. Ponds affected water quality and macroinvertebrate communities downstream. Exceedences of temperature and DO criteria occurred more frequently and were more severe downstream than upstream of ponds. Ponds in rural catchments increased mean daily stream temperatures 3.1–6.6°C during the critical summer period, and temperature differences were three times higher than those in bush catchments (0.8–2.0°C). Elevated temperatures were observed for hundreds of metres downstream owing to the slow rate of cooling (1°C/ 100 m), expanding the extent of adverse effects well beyond the “footprint” of the pond. Macroinvertebrate community composition (sample area 1–3 m 2 ) and values of four commonly used metrics appeared to be significantly affected by ponds in rural and native forest catchments. These finding have important management implications that should lead to modifications (e.g., breaching dams) of the estimated 4500 existing ponds in the Auckland region, where possible, and restrictions on proposals for new “on‐line” ponds.